2022
DOI: 10.1111/vox.13384
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for in vitro evaluation of blood components collected, prepared and stored in non‐DEHP medical devices

Abstract: Background and Objectives: DEHP, di(2-ethylhexyl) phthalate, is the most common member of the class of ortho-phthalates, which are used as plasticizers. The Medical Device Regulation has restricted the use of phthalates in medical devices. Also DEHP has been added to the Annex XIV of REACH, "Registration, Evaluation, Authorisation and Restriction of Chemicals" due to its endocrine disrupting properties to the environment. As such, the sunset date for commercialisation of DEHP-containing blood bags is May 27 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As a result, some DEHP might be present in the final hPL product depending on the amount of plasma. At the time of writing, DEHP is still allowed for manufacturing blood collection sets, but this will change in 2025 as per the EU Medical Device Regulation [54]. From then on, DEHP is only allowed to be used in medical devices below a concentration of 0.1% (wt/wt).…”
Section: Hpl Productmentioning
confidence: 99%
“…As a result, some DEHP might be present in the final hPL product depending on the amount of plasma. At the time of writing, DEHP is still allowed for manufacturing blood collection sets, but this will change in 2025 as per the EU Medical Device Regulation [54]. From then on, DEHP is only allowed to be used in medical devices below a concentration of 0.1% (wt/wt).…”
Section: Hpl Productmentioning
confidence: 99%
“…11 Studies have shown that DEHP, among other ortho phthalates, can leach out of the plastic and into the blood. 12 To protect the safety and well-being of patients, the European legislation has been implemented to ban the use of four phthalates, including DEHP, in medical devices including blood product bags/bag systems through amendments to the European Chemicals Agency (ECHA) Annex XIV of REACH. More specifically, as per the Commission Regulation 2023/2482, the sunset date of July 1, 2030 is applicable for DEHP-containing medical devices within scope of Regulations (EU) 2017/745 and (EU) 2017/746, which includes blood bag systems.…”
Section: Introductionmentioning
confidence: 99%
“…13 Materials devoid of DEHP or other harmful phthalates are now in various stages of development using alternative plasticizers (including 1,2-cyclohexane dicarboxylic acid diisononyl ester [DINCH], di(2-ethylhexyl) adipate [DEHA], and di(2ethylhexyl) terephthalate [DEHT]) to ensure the highest level of safety for blood transfusions. 12 The objective of this study was to evaluate the in vitro platelet quality and functionality of PCs produced using the Reveos system and pooled into a transfusable dose using the IMUGARD Platelet Pooling Set, using DEHP-free blood collection sets. Furthermore, we compared PCs produced from WB componentized from fresh and overnight-stored WB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations